Clinical associations with stage B heart failure in adults with type 2 diabetes. (July 2021) - Gulsin, Gaurav S.; Brady, Emer; Marsh, Anna-Marie; Squire, Gareth; Htike, Zin Z.; Wilmot, Emma G.; Biglands, John D.; Kellman, Peter; Xue, Hui; Webb, David R.; Khunti, Kamlesh; Yates, Tom; et al.
Background: There is a high prevalence of asymptomatic (American Heart Association Stage B) heart failure (SBHF) in people with type 2 diabetes (T2D). We aimed to identify associations between clinical characteristics and markers of SBHF in adults with T2D, which may allow therapeutic interventions prior to symptom onset. Methods: Adults with T2D from a multi-ethnic population with no prevalent cardiovascular disease [ n  = 247, age 52 ± 12 years, glycated haemoglobin A1c (HbA1c) 7.4 ± 1.1% (57 ± 12 mmol/mol), duration of diabetes 61 (32, 120) months] underwent echocardiography and adenosine stress perfusion cardiovascular magnetic resonance imaging. Multivariable linear regression analyses were performed to identify independent associations between clinical characteristics and markers of SBHF. Results: In a series of multivariable linear regression models containing age, sex, ethnicity, smoking history, number of glucose-lowering agents, systolic blood pressure (BP) duration of diabetes, body mass index (BMI), HbA1c, serum creatinine, and low-density lipoprotein (LDL)-cholesterol, independent associations with: left ventricular mass:volume were age (β = 0.024), number of glucose-lowering agents (β = 0.022) and systolic BP (β = 0.027); global longitudinal strain were never smoking (β = −1.196), systolic BP (β = 0.328), and BMI (β = −0.348); myocardial perfusion reserve were age (β = −0.364) and male sex (β = 0.458); and aortic distensibility were age (β = −0.629) and systolic BP (β = −0.348). HbA1c was not independently associated with any marker of SBHF. Conclusions: In asymptomatic adults with T2D, age, systolic BP, BMI, and smoking history, but not glycaemic control, are the major determinants of SBHF. Given BP and BMI are modifiable, these may be important targets to reduce the development of symptomatic heart failure.